Performance analysis of stock mutual funds using the Sharp method: Before and after the Covid-19 pandemic - Rina Tresnawati; Shinta Herawati; Syakieb Arsalan (New Applied Studies in Management, Economics & Accounting)
Mutual funds are an essential investment instrument in the financial markets that allow indirect investment with more controlled risks and returns, especially for investors just starting. The research aims to evaluate the performance of mutual funds in stock using the Sharpe method. The purposive sampling technique is the technique used in this research with specific criteria and succeeded in collecting 210 stock mutual fund samples. The research results show that the performance of mutual funds in stock was negative during 2018-2020, but it improved to positive in 2021. In 2021, the performance of mutual funds exceeded benchmark standards or was outperformed. The hope of conducting this research is that it can and will help investors make investment decisions related to stock mutual funds.